2012
DOI: 10.5897/ajb11.2786
|View full text |Cite
|
Sign up to set email alerts
|

Barley breeding for quality improvement in Tunisia

Abstract: This study was initiated to assess the effectiveness of three selection procedures applied in the early segregating generations of barley crosses for quality traits. The selection procedures were pedigree selection (PS), bulk selection (BS) and single seed descent selection (SSD). Selection was operated in F 2 's crosses. Field trials were conducted with 19 F 3 crosses of barley in two different environments, a sub-humid environment at Beja and a semi-arid one at Kef. Heading date (HD), thousand kernel weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Accordingly, with respect to PHmat, genotypes G12, G2, and G50 occurred in two or more environments, while the remaining genotypes showed specific adaptation. In barley breeding trials, Medimagh et al (2012) reported that based on the top four AMMI selections under different breeding methods, it was found that the pedigree method for high-input environments was the best method to screen for high yield potential. In sorghum yield trials, Hailemariam and Tesfaye ( 2019) found both wide and specific adaptations for seed yield.…”
Section: Top Four Ammi Selectionsmentioning
confidence: 99%
“…Accordingly, with respect to PHmat, genotypes G12, G2, and G50 occurred in two or more environments, while the remaining genotypes showed specific adaptation. In barley breeding trials, Medimagh et al (2012) reported that based on the top four AMMI selections under different breeding methods, it was found that the pedigree method for high-input environments was the best method to screen for high yield potential. In sorghum yield trials, Hailemariam and Tesfaye ( 2019) found both wide and specific adaptations for seed yield.…”
Section: Top Four Ammi Selectionsmentioning
confidence: 99%
“…In less developed Mediterranean countries such as Tunisia, barley plays a key role as its grain and straws are the principal feed for livestock. Small ruminants such as sheep and goats are the main livestock in Tunisia, representing a valuable dietary contribution in rural areas and a principal economic output (Medimagh et al, 2012). Genetic improvement to increase yield is underway in the Tunisian breeding program.…”
Section: Introductionmentioning
confidence: 99%